БАТІМЕТРІЧНИЙ РОЗПОДІЛ ЖИВИХ АКТИВНИХ ФОРМ ЗООБЕНТОСУ В ХЕМОКЛІНІ ЧОРНОГО МОРЯ - Гулiн, М. Б. (Marine Ecological Journal, 2023)
The intravital observations of micro- and meiobenthos in the redox-gradient benthic zone of the deep shelf and upper continental slope of the Black Sea have been carried out. In the Bosphorus area, highest abundance of alive, locomotory-active individuals was found at depth of 172 m – above the upper margin of the Black Sea’s hydrogen sulfide zone adjacent to the continental slope (185 – 188 m). At the gentler slope of sea floor in the NW Black Sea, within the suboxic and redox zones, it was also observed the accumulation of microaerophilic benthic organisms that’s characterized by two peaks with the maximum density. These detected features of benthos location could be associated with sea-floor topography, local water stratification as well as spatio-temporal dynamics of water masses.